ISSR Marker Based Population Genetic Study of Melocanna baccifera (Roxb.) Kurz: A Commercially Important Bamboo of Manipur, North-East India - Heikrujam Nilkanta; Thoungamba Amom; Leimapokpam Tikendra; Hamidur Rahaman; Potshangbam Nongdam (Scientifica)
Melocanna baccifera (Roxb.) Kurz is an economically important bamboo of North-East India experiencing population depletion in its natural habitats. Genetic variation studies were conducted in 7 populations sampled from 5 districts of Manipur using ISSR molecular markers. The investigation was carried out as a primary step towards developing effective conservation strategies for the protection of bamboo germplasm. ISSR marker analysis showed significant level of genetic variation within the populations as revealed by moderately high average values of Nei’s genetic diversity (H 0.1639), Shannon’s diversity index (I 0.2563), percentage of polymorphic bands (PPB 59.18), total genetic variation (Ht 0.1961), and genetic diversity within population (Hs 0.1639). The study also divulged a high genetic variation at species level with Shannon’s diversity index (I), Nei’s genetic diversity (H), and percentage of polymorphic band (PPB%) recorded at 0.3218, 0.1939, and 88.37, respectively. Genetic differentiation among the populations (Gst) was merely 19.42% leaving 80.58% of genetic variation exhibited within the populations. The low genetic diversity between populations was consistent with AMOVA. The low genetic differentiation among populations coupled with existence of significantly high genetic diversity at species level indicated the urgent necessity of preserving and protecting all the existing natural bamboo populations in the region.